Analysing the flows and labour market outcomes of short-term mobile workers in the EU - Wouter Zwysen; Mehtap Akgüç (European Trade Union Institute (ETUI), 2023)
While labour flows within the EU are substantial and growing, relatively little is known about what drives them or what conditions mobile workers face. This working paper describes the flows of working-age movers between EU Member States, addressing the question of who decides to move and whether these moves follow similar push and pull factors to migration more generally. Besides investigating why EU citizens move between countries, we also describe their initial labour market outcomes at the destination, which is important in considering the benefit of such moves. Our analyses indicate substantial variation in labour market outcomes. As with other migration, mobility within Europe is usually associated with relatively worse labour market opportunities in the labour market compared to the majority. There is strong variation between movers depending on region within the EU, however. This paper also compares the situation of recent movers to those who stay in their countries of origin, finding large differences between countries in the selection of movers.
Keywords: 330; intra-EU flows; short-term mobility; labour market integration; migration